Electrical properties and phase transition behaviors of Sr-doped 0.8PZT-0.2PNN ceramics - Eitssayeam S. (2014)
Dielectric properties and phase transition behaviors of Sr-doped 0.8PbZr1/2Ti1/2O3-0.2PbNi1/3Nb2/3O3 ceramics have been investigated. The ceramics were prepared by a normal solid-state method. For undoped sample, very high relative permittivity >30,000 (at 1 kHz) was observed at the transition temperature of 278 °C. With increasing Sr concentration, the degree of diffuse phase transition was enhanced and a linear reduction in the transition temperature was produced. © 2007 Elsevier B.V. All rights reserved.